Territori e piani dopo la crescita Una esperienza di conoscenza e di progetto nella Puglia dell'innovazione - CALACE, Francesca (Territori, 2021)
The purpose of the book is, on one hand, to try to trace a method and some working perspectives for post-growth planning, and on the other hand, to testify, through a concrete experience, the old and new questions and the interpretative and visionary effort that the territory poses to planning today. In a region like Apulia, which has followed an innovative path in the government of the territory and the landscape, the experience of knowledge and project for the city of Ugento is an opportunity to reflect on how today the construction of the plan can accompany the government of the territory in its development, rather than claiming to direct it, penetrate its policies and interact with its various instruments in a dynamic and even experimental way. In this way the construction of the plan can provide for a system of values to refer to in order to navigate the change and the design vision to be placed at the base of urban policies, tactics, individual interventions, thus coming to be a tool at the service of local development.